Poster 235: Surgical Management of Patellar Instability in Adolescents with High Grade Trochlear Dysplasia. Issue 7 (30th July 2022) - Nunally, Kianna; Cook, Danielle; Hussain, Zaamin; Zheng, Evan; Yen, Yi-Meng; Kramer, Dennis; Micheli, Lyle; Kocher, Mininder; Heyworth, Benton; Wilson, Benjamin
Objectives: High-grade trochlear dysplasia (HGTD) has previously been identified as a risk factor for failure of surgical management of patellofemoral instability (PFI). However, limited data exists on the influence of the type of surgical procedure performed on postoperative outcomes in these patients. The purpose of this study was to identify the rates of failure of primary PFI surgery in patients with HGTD compared to those without HGTD and to assess the effect of the type of surgery on recurrent instability and return to OR. Methods: We retrospectively reviewed patients aged ≤19 years who underwent primary surgery for PFI at our institution between 2008 and 2017. Patients underwent procedures including medial retinacular plication (MRP), medial patellofemoral ligament reconstruction (MPFLR), tibial tubercle osteotomy (TTO), or combined procedures. We excluded patients with incomplete imaging data, BMI >30kg/m 2, those that underwent surgery for fixation of a chondral fracture >1cm, and patients with a diagnosis of syndromic disorder. Trochlear dysplasia was evaluated based on pre-operative MRI. Patients were divided between those that had HGTD and those without HGTD. Comparisons were made between the two groups and logistic regression analysis was utilized to determine if surgery category was associated with rate of recurrence in the HGTD patients. Results: Three-hundred three patients, average age 15.1 years, underwent primary surgical stabilization for PFI with median follow up time of 3.0 years. Forty-nine percent (149/303) of the cohort had HGTD. Demographics were comparable between HGTD groups (Table 1). When compared to the patients without HGTD, patients with HGTD showed similar rates of recurrent instability, return to the OR for instability, and return to the OR for other reasons. Looking at patients with just HGTD, there was a significant association between surgery type and outcomes (Table 2). HGTD patients who underwent MPFLR had a 63% decrease in the odds of experiencing recurrent instability compared to those undergoing MRP (OR=0.37; p=0.03). Similarly, the TTO surgery group had an 80% decrease in the odds of experiencing recurrent instability compared to patients undergoing MRP (OR=0.20; p=0.002). Conclusions: While adolescents with PFI and HGTD overall have similar results after surgical stabilization, there is a significant effect of the type of surgery performed. Patients with HGTD that underwent MRP had significantly more instability and return to the OR for instability surgeries than patients that underwent other procedures. Based on this data, adolescents with PFI and HGTD should be considered for more powerful surgeries to limit the risk of recurrence or return to the OR. Table 1. Patient Demographics and Outcomes Compared Between Trochlear Dysplasia Groups (n=303) Table 2. Outcomes of Patients with HGTD Compared by Type of Surgery (N=149).